Correction: Panjideh et al. Improved Therapy of B-Cell Non-Hodgkin Lymphoma by Obinutuzumab-Dianthin Conjugates in Combination with the Endosomal Escape Enhancer SO1861. Toxins 2022, 14, 478 - Hossein Panjideh; Nicole Niesler; Alexander Weng; Hendrik Fuchs (Toxins, 2022)
The authors wish to make corrections to their paper [...]